2015
DOI: 10.1175/mwr-d-15-0154.1
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Horizontal and Vertical Grid Spacing on Mixing in Simulated Squall Lines and Implications for Convective Strength and Structure

Abstract: The sensitivity of an idealized squall line to horizontal D h and vertical D y grid spacing is investigated using a new approach. Simulations are first performed at a horizontal grid spacing of 1 km until the storm reaches its mature stage. The model output is then interpolated to smaller (and larger) grid spacings, and the model is restarted using the interpolated state plus small thermodynamic perturbations to spin up small-scale motions. This framework allows an investigation of the sensitivity of the storm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
105
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 105 publications
(113 citation statements)
references
References 47 publications
8
105
0
Order By: Relevance
“…This is plotted in Figure b, which shows that H has some resolution dependence, but asymptotes to roughly 500 m at fine resolution. Plugging H=500 m and ngray=2 into equation yields dx=250 m for the inner edge of the gray zone, in good agreement with Figure a as well as Lebo and Morrison ().…”
Section: Criterion For the Convection‐resolving Regimesupporting
confidence: 84%
See 1 more Smart Citation
“…This is plotted in Figure b, which shows that H has some resolution dependence, but asymptotes to roughly 500 m at fine resolution. Plugging H=500 m and ngray=2 into equation yields dx=250 m for the inner edge of the gray zone, in good agreement with Figure a as well as Lebo and Morrison ().…”
Section: Criterion For the Convection‐resolving Regimesupporting
confidence: 84%
“…Our focus here will be on the effects of horizontal resolution on parcel aspect ratio D / H and hence vertical acceleration, as opposed to the effects of horizontal resolution on turbulence and entrainment (e.g., Bryan et al, ; Bryan & Morrison, ; Lebo & Morrison, ; Wyngaard, ). These effects are likely related, though, as Lebo and Morrison () find that the onset of resolved turbulent mixing and the convergence of vertical motion coincide at dx=250 m. This gives a tentative answer to question 1 above, but the answer is purely empirical.…”
Section: Introductionmentioning
confidence: 99%
“…With these grid spacings, entrainment may not be produced sufficiently (Bryan et al, ; Bryan & Morrison, ). Furthermore, statistical convective properties have been shown not to converge until the grid spacing was reduced to 250 m for an idealized squall line (Lebo & Morrison, ). However, computational limitations prevented us from further decreasing the horizontal grid spacing for these simulations.…”
Section: Methodsmentioning
confidence: 99%
“…Since the background CO profile is reinitialized at 21 UTC from observations, the correct WRF-Chem mean inflow and outflow values indicate that the model is representing the transport adequately. However, Lebo and Morrison [2015] determined that a horizontal grid spacing of 250 m was necessary for convergence of statistical convective properties and mixing in WRF simulations of idealized squall lines. Bryan et al [2003] and Bryan and Morrison [2012] found that entrainment in a numerical model similar to WRF was underestimated at a horizontal grid spacing of 1 km, due to the inability to properly resolve turbulent eddies.…”
Section: Scavenging Efficienciesmentioning
confidence: 99%